Search for new regulators of sugar pea plant growth among synthetic pyrimidine derivatives - Minaieva, Inna; Tsyhankova, Viktoriia; Pilo, Stepan; Kliuchko, Svitlana; Brovarets, Volodymyr (Problems of Environmental Biotechnology, 2021)
The search for new regulators of sugar pea growth among synthetic pyrimidine derivatives was carried out.